(untitled) (Economic and Political Thought, 2016)
This text is an analysis of selected aspects of public policies in the field of health care in developed countries. They are tested for implementation of the Governance concept. The aim of the study is to show the results of this analysis as a catalogue of good practices, which can provide recommendations for other countries, because implementation of governance is an opportunity to create effective policies in the social area.